DYNAMICS OF CULTURAL GLOBALIZATION: CULTURAL CONFLICT, CULTURAL SYNTHESIS - Evgeny A. Avdeev; Evgeny L. Budarin (Вестник Северо-Кавказского федерального университета)
The article deals with socio-cultural dynamics of globalization, analyzes interaction of global and local cultures. The authors review the relationship of integration and disintegration processes in modern society.